2014 Eighteenth National Power Systems Conference (NPSC) 2014
DOI: 10.1109/npsc.2014.7103814
|View full text |Cite
|
Sign up to set email alerts
|

Initialization of DFIG based wind generating system

Abstract: Doubly fed induction generator (DFIG) has to be properly initialized for performing dynamic analysis. Even though DFIG has independent real and reactive power control, the real and reactive power output of DFIG depends both on the machine side parameters like wind speed and slip and network side parameters like grid voltage etc. This paper proposes a method for obtaining power flow solution incorporating DFIG based wind generation with only four variables as unknown variables as compared to other literature wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the study of Slootweg, Polinder, and Kling, it is shown a procedure to initialize WTs with different electrical generators for power system dynamic simulations, but it makes reference to an iterative process to obtain the final solution. In the study of Amutha and Kalyan, a method for obtaining steady‐state solution with four unknown variables is presented, but this method is based on power flow analysis, so the DFIG is modeled using a reduced‐order model (from the point of view of an electrical power system). A recent method proposed by Wu and Xie suggests calculating steady‐state operating conditions for eigenvalue analysis of DFIG‐based WTs without making use of an iterative process, just by ignoring the dynamic terms of the equations.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Slootweg, Polinder, and Kling, it is shown a procedure to initialize WTs with different electrical generators for power system dynamic simulations, but it makes reference to an iterative process to obtain the final solution. In the study of Amutha and Kalyan, a method for obtaining steady‐state solution with four unknown variables is presented, but this method is based on power flow analysis, so the DFIG is modeled using a reduced‐order model (from the point of view of an electrical power system). A recent method proposed by Wu and Xie suggests calculating steady‐state operating conditions for eigenvalue analysis of DFIG‐based WTs without making use of an iterative process, just by ignoring the dynamic terms of the equations.…”
Section: Introductionmentioning
confidence: 99%